Analysis of the Criminalization of Violating Acts Legal Sociology in the Era of Modern Globalization - Fadhilah Nur Ramadhani; Yoga Bagus Adhitya; Uday Adi Junaedi; Sigit Gunawan; Diky Dikrurahman (Riviera Publishing, 2024)
The modern era of globalization has brought significant changes in various aspects of life, including in the legal field. Rapid technological developments and increasingly close interconnections between nations have created various new challenges for law enforcement. One of the challenges that arises is the criminalization of actions that violate legal sociology. The aim of this research is to conduct an analysis of the criminalization of unlawful behavior within the framework of legal sociology in the era of modern globalization. This research uses non-doctrinal research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that forms of criminalization that violate legal sociological norms in the era of modern globalization include drugs, prostitution, pornography, vandalism, religious blasphemy and white collar crime. Criminalization of acts that violate legal sociology in the era of modern globalization is a complex issue that has a significant impact on human rights, social justice and social interaction. Efforts to prevent these acts require multi-faceted efforts involving various stakeholders, such as government, law enforcement, civil society and academics. Implications of the research, the findings of this research underscore the necessity for a holistic approach in addressing the criminalization of actions that violate legal sociology. Policymakers must consider the social and cultural contexts of criminal behavior to develop effective laws and regulations.